Tragedi bencana sumatera: korban tewas capai 1.006 orang dan upaya penyelamatan - Darmayanti, Silvi Nur Afifa (Maliki Interdisciplinary Journal, 2026)
The hydrometeorological disaster tragedy of flash floods and landslides that struck the provinces of Aceh, North Sumatra, and West Sumatra since late November 2025 is one of the deadliest events in contemporary Indonesian history. Triggered by extreme rainfall influenced by Tropical Cyclone Senyar and anthropogenic factors such as massive deforestation and illegal mining, this disaster caused widespread damage to infrastructure, settlements, and agricultural land in mountainous and lowland areas. As of December 13, 2025, the National Disaster Management Agency (BNPB) recorded a total of 1,006 deaths, with approximately 415 in Aceh, 349 in North Sumatra, and 242 in West Sumatra. In addition, 217 people are still listed as missing, more than 5,400 injured, and hundreds of thousands of homes severely damaged, forcing nearly 900,000 residents to evacuate. Vulnerable groups such as children and the elderly are the most affected, with secondary risks such as disease outbreaks and psychological trauma. Rescue and emergency response efforts were intensively carried out by the National Disaster Management Agency (BNPB), the Indonesian National Armed Forces (TNI), the Indonesian National Police (Polri), the National Search and Rescue Agency (Basarnas), and thousands of volunteers, with international support from UNICEF and the WHO. Search operations using helicopters, drones, and heavy equipment successfully evacuated tens of thousands of people, while logistics distribution reached hundreds of tons of food, medicine, and tents. The rehabilitation phase began with river normalization, emergency infrastructure development, and long-term mitigation plans such as reforestation and an early warning system. This disaster highlighted Indonesia’s vulnerability to climate change and the need for sustainable environmental management. Strong national solidarity provided hope for a more resilient reconstruction, ensuring that the lessons from this tragedy inform future prevention policies.